Legislative Definition of Spam for New Zealand - Kellett, Simon (Victoria University of Wellington Law Review, 2005)
This article discusses the phenomenon of spam with the intention of providing a practical definition of the concept for use in anti-spam legislation. The billions of e-mails that are classified as spam every year affect the majority of the world’s e-mail users, and apart from causing annoyance these unwanted communications create significant economic costs. Filtering and downloading spam wastes both time and money, and governments around the world are beginning to react to the problem with legislation to reduce the volume of spam and penalise those who deal in this medium. The problem is how to define "spam" without punishing legitimate commercial e-mails and other unsolicited e-mails that, while not specifically requested, are not unwanted. The author supports an "opt-in" regime with the defences of consent and conspicuous publication available to prevent undue curtailment of the freedom of expression guaranteed by the New Zealand Bill of Rights Act 1990. This approach is encompassed in draft legislation set out at the end of the article.